Effects of maternal smoking on human placental vascularization: A systematic review - Daniela Pintican; Alexandra Andreea Poienar; Stefan Strilciuc; Dan Mihu (Elsevier, 2019)
The abnormal development of placental vascularization leads to placental insufficiency, which further reduces the nutrient and trace exchange between maternal circulation and fetal circulation. These changes cause maternal and fetal complications. The objective of our systematic review was to explore the effects of maternal smoking on placental vascularization. The eligibility criteria were: articles with experimental, quasi-experimental or observational design, performed on human subjects, that study the association, correlation or causation between maternal smoking and changes in placental vascular network. A total of 33 full-text papers were assessed for eligibility, resulting in 12 original articles that were included in the systematic review. Doppler studies confirm reductions in blood flow velocity waveforms and increase in RI in the uterine, umbilical and fetal middle cerebral arteries. These findings are confirmed by morphometric measurements of fetal capillaries in villi that were shown to be smaller in smoke exposure groups. Keywords: Doppler, Fetal, Pregnancy, Smoking